Promoting mental wellbeing in pregnant women living in Pakistan with the Safe Motherhood-Accessible Resilience Training (SM-ART) intervention: a randomized controlled trial - Shireen Shehzad Bhamani; An-Sofie Van Parys; David Arthur; Nicole Letourneau; Gail Wagnild; Olivier Degomme (BMC, 2024)
Abstract Background The negative impact of adverse perinatal mental health extends beyond the mother and child; therefore, it is essential to make an early intervention for the management of mental illness during pregnancy. Resilience-building interventions are demonstrated to reduce depression and anxiety among expectant mothers, yet research in this field is limited. This study aims to examine the effect of the 'Safe Motherhood-Accessible Resilience Training (SM-ART)' on resilience, marital adjustment, depression, and pregnancy-related anxiety in a sample of pregnant women in Karachi, Pakistan. Method In this single-blinded block randomized controlled study, 200 pregnant women were recruited and randomly assigned to either an intervention or a control group using computer-generated randomization and opaque sealed envelopes. The intervention group received the SM-ART intervention consisting of six, weekly sessions ranging from 60 to 90 min. Outcomes (Resilience, depression, pregnancy-related anxiety and marital harmony) were assessed through validated instruments at baseline and after six weeks of both intervention and control groups. Results The results revealed a significant increase in mean resilience scores (Difference:6.91, Effect size: 0.48, p-value < 0.05) and a decrease in depressive symptoms (Difference: -2.12, Effect size: 0.21, p-value < 0.05) in the intervention group compared to the control group. However, no significant change was observed in anxiety and marital adjustment scores. Conclusion The SM-ART intervention has the potential to boost resilience scores and decrease depressive symptoms in pregnant women and offers a promising intervention to improve maternal psychological health. Trial registration NCT04694261, Date of first trial registration: 05/01/2021.